MURAL MELATIH KREATIVITAS VISUAL ANAK USIA DINI (STUDI KASUS TK FAJAR HARAPAN) - Suryawan I Gde; Sindu Putra Ida Bagus Komang; Suyasa Ariputra I Putu (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
Murals are one of the alternative media for street visual art/street visual art that functions as a forum for people's aspirations through paintings. The attractiveness of art gives a strong impression, in line with visual communication theory which assumes that the use of art in educational media is very important. One of these forms of art is a mural. The purpose and function of the mural itself are still developing today. The making of murals in early childhood schools is basically a form of utilizing empty space by incorporating educational missions, such as: as a medium for recognizing local cultural values (folklore). Because folklore, indirectly represents the social reality that is around us. Thus basically the implicit function of making murals in empty spaces in early childhood schools is to train students' sensitivity. The environment is a factor that can affect a child's imagination. By placing murals on the walls of early childhood schools, apart from functioning as decoration, indirectly has the function of stimulating children's sensitivity to visuals. This visual sensitivity indirectly develops children's imagination. Thus, murals can stimulate the imaginary environment or imaginary world of children that penetrate the developer of their imagination. Art will always develop, which will be the source of ideas in the process of its creation. Like children who are inspired by murals in creating their works. Seeing this, students will be more open and sensitive to the environment around us so that new ideas will emerge fresh and close to us as a source of ideas for creating works.